Development and Psychometric Validation of an Instrument for Assessing the Quality of Teachers’ In-Service Training - Yaghmori, Vahid; Mirzaei, Nooraldin; Mojtabazadeh, Mohammad (Assessment and Practice in Educational Sciences, 2026)
This study aimed to develop and psychometrically validate an instrument for assessing the quality of teachers’ in-service training programs. A mixed-methods approach (qualitative–quantitative) was employed, integrating in-depth qualitative data with quantitative evidence. In the qualitative phase, semi-structured interviews were conducted with teachers, school principals, and education experts to identify components, categories, and interrelationships within in-service training programs. Based on these findings, a 30-item questionnaire was developed and administered to 384 participants to evaluate the instrument’s validity and reliability. First-order factor analysis revealed item factor loadings ranging from 0/58 to 1/00, while second-order factor analysis indicated loadings for the main dimensions between 0/98 and 1/10, demonstrating high explanatory power and structural validity. The ten main dimensions—Smart Professional Needs Assessment, Advanced Pedagogical Design, Smart Digital Learning, Innovative Smart Methods, Sustainable Professional Development, Smart Educational Evaluation, Learning Organizational Support, Networked Professional Collaboration, Educational Digital Inclusion, and AI Literacy in Education—played the most significant role in explaining the quality of in-service training. Results further confirmed strong convergent and discriminant validity, with high internal consistency (α=0/958–0/996, AVE=0/921–0/996). Findings suggest that the instrument can comprehensively evaluate multiple aspects of in-service training and identify key indicators affecting program quality, such as self-directed learning and the integration of digital and AI-based educational technologies. Overall, this study demonstrates that the developed instrument provides a valid, reliable, and systematic framework for assessing the effectiveness of in-service teacher training and offers practical applications for educational managers and policymakers in designing, implementing, and monitoring these programs.